DESAIN PENANAMAN NILAI-NILAI KEAGAMAAN BERBASIS KELUARGA - Purim Marbun (Bethel Press, 2023)
This article aims to provide a simple explanation of the duties and responsibilities of the family in instilling religious values ​​as the foundation for religious moderation in the Indonesian context. The background of this research is that the emergence of various intolerance actions in this country that tend to wear religious clothes as a shield cannot be denied, it is undeniable that the family is negligent in providing the basics of true faith coupled with adequate education regarding respect and respect for fellow believers. The writing method used in this article is a literature study which will dissect and analyze various ideas and concepts to produce a design for instilling values ​​in sowing family-based religious moderation. The results of this study answer that the inculcation of religious values ​​in the family will also build an attitude of moderation in one's religion when outside the family environment both at school and elsewhere.